Materials for Energy Conversion Systems: Fundamentals, Designs, and Applications - Cicconi, Maria Rita; Hayakawa, Tomokatsu; Dkhil, Brahim; Alexe, Marin (Physica Status Solidi-Rapid Research Letters, 2024)
This Special Section is related to the Symposium B “Materials for energy conversion systems: fundamentals, designs, and applications” of the European Materials Research Society Spring Meeting 2023, organized by Maria Rita Cicconi, Tomokatsu Hayakawa, Brahim Dkhil, and Marin Alexe. The symposium addressed a variety of materials and technologies that are essential for the development of state-of-the-art coupled energy conversion systems. Indeed, the development of alternative coupled energy conversion systems, i.e. the simultaneous conversion of energy from mechanical and optical fields, requires an understanding of the multifaceted phenomena that occur in materials at different length scales. The symposium received the highest number of submissions, with over 360 abstracts submitted for individual presentations (oral, poster, and invited). Due to the large number of submissions, 10 oral sessions and 3 poster sessions were organized, covering a wide variety of materials for energy conversion, and both fundamental aspects and technological developments based on multimodal energy sources, such as electro-mechanical and electro-optical coupled systems. 22 invited speakers provided the opportunity to discuss the latest hot-topic, presenting their scientific results but also their perspectives. The contributions to this Special Section perfectly reflect that energy is one of the major scientific and engineering challenges of our time. In fact, more than ever, there is a growing global awareness of the need for new technologies related to efficient energy storage and conversion. When we talk about environmentally friendly and renewable energy sources, solar energy is the first thing that comes to mind. Article 2300233 contributes to the Special Section by reporting on the development and investigation of multifunctional inorganic pigment coatings with photocatalytic activities, while 2300236 deals with solar hydrogen generation using HI solution and single-walled carbon nanotubes. In the area of thin-film photovoltaics, article 2300239 explores dark degradation and typical metastabilities in commercial thin-film devices, while 2300293 develops novel Langmuir-Schaefer films and combines theoretical calculations to provide an advanced characterization of the optoelectronic properties in these films. Other promising materials for optoelectronic applications are the metal halide perovskites, and article 2300241 presents the structural and optical investigation of lead-free mixed halide Bi-based perovskites synthesized by a hydrothermal method. Lead-free perovskites received special attention throughout the symposium as these materials are the green alternative to the lead-based ones and have clearly demonstrated multifunctionality, such as ferroelectricity in electro-optic materials and photovoltaic response in ferroelectrics. Examples of the strong interest in these materials are reported in articles 2300290 and 2300292 that deal with barium titanate materials. Perovskites have also been explored as multifunctional host crystals for phosphor-converted white light-emitting diodes, and article 2300237 uses machine learning to determine the color purity of Eu3+ perovskite phosphors. In addition to energy conversion, storage is also an open challenge, and article 2300211 reports an example of the development of an optimized hybrid supercapacitor. Many of the papers in this Special Section combine the development of novel materials or novel experimental approaches with state-of-the-art simulations, demonstrating that interdisciplinary synergies are the way to improve and accelerate the development of cutting-edge applications and devices. We hope that the symposium provided a unique opportunity for exchange and collaboration, which is essential to foster a multiscale and multidisciplinary dialogue on innovative and sustainable materials in the field of energy conversio